An Analysis of Maxim Relevance by Main Character in Taxi Driver Film - Risa Maulana Ishaq; I Gde Agoes Caskara Surya Putra (CV Wahana Publikasi, 2023)
When a speaker ignores maxims of the principle of cooperation or fails to convey the hidden meaning of an utterance, this phenomenon is known as maxim disrespect. The disregarded maxim of the movie “Taxi Driver” is the subject of this study. Taxi Driver is a 1976 American drama and crime film directed by Martin Scorsese. This study is intended to identify the relevance of various ignoring maxims that appear in the film and to explain their occurrence. Ignorance of relevance occurs because the interlocutor must be as true as necessary or convey information based on what is happening in real life. Researchers draw on ideas from Grice’s Principle of Cooperation (1975). This study uses direct observation methods and qualitative descriptions in data analysis. As a result, the movie The Taxi Driver has at least 19 flouting maxim data, of which there are five results from the maxim relevance obtained from the conversational dialogue on the main character. From the 5 data, the author has also provided an analysis and answered various possibilities for the occurrence of flouting relevance either from the views of the speaker or listener. Flouting relevance occurs because the participants of the conversation have to be as truthful as required or should give the information based on what happens in real life. To sum up, there are various reasons why the character flouts relevance, including jokes and denial of a statement. However, it all returns to each character’s role, which makes the scene more perfect.